Faktor Risiko Yang Berhubungan Dengan Kejadian Myalgia Pada Buruh Harian Sawit di Desa Sukajaya Kecamatan Kotawaringin Lama Kabupaten Kotawaringin Barat Provinsi Kalimantan Tengah Tahun 2011 - Yulia Christina; Yamtana Yamtana; Haryono Haryono (Poltekkes Kemenkes Yogyakarta, 2011)
The activities of palm oil daily workers which are carried out manually is at risk to causing muscle pain or myalgia. The other factors contribute to this con-dition are the unsupported physical environment, workers’ endurance, and the incompatiblity between work load and work capacity. The study was aimed to determine the risk factors correlated with myalgia among pal oil daily workers at Sukajaya Village of Kotawaringin Lama Subdistrict. The observed depen-dent variables were age, sex, status within family, workload, period of employ-ment, distance of workplaces, and transportation modes, and the data were collected by following cross sectional design. The study sample were all daily workers who work for PT BGA i.e.139 person. The data were obtained through questionnaires, direct interviews and physical examinations of the pulse rate measurements when they were working. The data were analyzed uni-variately and by using chi square test for bivariate analysis. The results showed that risk factors of myalgia were female gender (p<0,001; OR = 4.588 and 95% CI: 2.132 to 9.872), and status within the family as housewive (p<0,001; OR = 3.908 and 95% CI: 1.835 to 8.325).